Pengaruh Persentase Campuran Serat Daun Nanas dan Cangkang Kerang Darah terhadap Inovasi Papan Partisi Penyekat Ruangan - Amalia, Nurul Afifah; Widyasari, Sheny; Setiabudi, Bambang; Fauziyah, Shifa (Civil Infrastructure Engineering and Architectural Design, 2023)
Indonesia's increasing population is a crucial problem. According to the Central Bureau of Statistics (2021), Indonesia's population growth in 2020 will increase by 32.56 million people. In line with the need for housing in Indonesia, as a result the available land is decreasing, so many housing developments use partitions. However, partitions on the market still have many drawbacks. Utilization of pineapple leaf fiber as a substitute for fiber and blood clam shell waste as a substitute for cement is certainly a solution to this problem. Where pineapple leaf fiber has a carbon content such as 23.39% cellulose, 42.72% hemicellulose, and 4.03% lignin. Blood clam shells contain Sio2 of 8.252% and CaCO3 ranging from 66-98%. The purpose of this study was to determine the effect of the use of these two materials on the partition characteristics produced through physical tests and mechanical test. Samples were made in laboratory studies with variations of pineapple leaf fiber subs 0%;30%;70%;100% with the number of samples for each mold size being 3 samples. Through the results of tests that have been carried out, the best variation of pineapple leaf fiber substitution is the 70% variation. This test was also carried out by comparing several commercial partitions (gypsum, kalsiboard and GRC).